2007
DOI: 10.1007/s00296-007-0321-x
|View full text |Cite
|
Sign up to set email alerts
|

Nitric oxide levels and the severity of juvenile idiopathic arthritis

Abstract: In this study, we evaluate the distribution of nitric oxide (NO) in the serum of juvenile idiopathic arthritis (JIA) patients, correlating it with parameters of the severity of the disease. Ninety-seven patients with mean age 11.7 years and disease duration 4.8 years, showing active disease or not, grouped as oligoarticular (n = 34), polyarticular (n = 29) and systemic (n = 34) group, presenting uveitis and positive RF with erosive arthritis or active disease and erosions had significantly high levels of NO th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
2
6
0
Order By: Relevance
“…Our study indicated a significant positive correlation between JADAS-27 and ESR and NO end-products’ levels, which is in concordance with previous authors’ observations in adult patients with RA; however, in JIA such correlations were not found [3, 9, 18]. On the other hand, it was observed by Bica et al that patients with active JIA and erosive disease had significantly higher NO levels, whereas children with an inactive rheumatoid process had similar NO levels regardless of whether erosions were present or not [3]. …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our study indicated a significant positive correlation between JADAS-27 and ESR and NO end-products’ levels, which is in concordance with previous authors’ observations in adult patients with RA; however, in JIA such correlations were not found [3, 9, 18]. On the other hand, it was observed by Bica et al that patients with active JIA and erosive disease had significantly higher NO levels, whereas children with an inactive rheumatoid process had similar NO levels regardless of whether erosions were present or not [3]. …”
Section: Discussionsupporting
confidence: 93%
“…Similarly to Bica et al and Lotito et al, we showed that the concentration of NO end-products in sera of children with JIA and active disease was higher than that in children with inactive process, however without a statistically significant difference [3, 17]. Our study indicated a significant positive correlation between JADAS-27 and ESR and NO end-products’ levels, which is in concordance with previous authors’ observations in adult patients with RA; however, in JIA such correlations were not found [3, 9, 18].…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Nevertheless, at central level, eNOS within the dorsolateral peri-aqueductal gray matter plays a differential role in the cardiovascular system during heat-and cold-mediated nociception via modulating glutamatergic/GABAergic neurotransmission [Chaitoff et al, 2008]. However, the effect of NO on pain and analgesia in the periphery remains contradictory [Durate et al, 1990;Holthusen and Arndt, 1994;Berrazueta et al, 1996;Aley et al, 1998;Bica et al, 2007;Brisby et al, 2007;Guan et al, 2007]. For example, eNOS expression in DRG was unaltered in a mouse spinal ligation model (a neuropathic pain model) while nNOS was increased [Guan et al, 2007].…”
Section: Discussionmentioning
confidence: 99%
“…This would be similar to the effect on cartilage explant cultures reported for undigested indomethacin in dimethyl sulfoxide (DMSO) (Arsenis & McDonnell, 1989; Frean et al. , 2002; Bica et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%